Local development and social responsibility of NGOs for international cooperation in sustainable community projects - Chiriboga Mendoza, Fidel Ricardo; Montagud Mayor, Xavier; Zambrano Pilay, Enrique Cristóbal (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
NGOs play a crucial role in promoting equitable and sustainable development, strengthening local capacities, fostering community participation, and working in alignment with the SDGs. International cooperation facilitates the effective implementation of these projects, enabling the transfer of resources and necessary knowledge to promote sustainable and balanced development. This systematic review examined the role of local development and social responsibility of non-governmental organizations (NGOs) in international cooperation for sustainable community projects. Exhaustive searches were conducted in academic databases, and relevant studies addressing these topics were selected. In terms of local development, NGOs focus on strengthening local capacities, promoting community participation, and supporting long-term self-sufficiency. They implement projects that promote economic, social, and environmental development in communities, considering local needs and specificities. Regarding social responsibility, NGOs commit to acting ethically and sustainably, ensuring transparency in their actions and being accountable to communities and donors. Additionally, they align with the principles of the United Nations Sustainable Development Goals (SDGs), working to promote equity, social justice, and sustainability globally. International cooperation plays a fundamental role in the success of these sustainable community projects, enabling the transfer of resources, knowledge, and best practices among different actors and countries